Molecular mechanism and therapeutic targeting of necrosis, apoptosis, pyroptosis, and autophagy in cardiovascular disease. Issue 22 (20th November 2021) - Li, Pan; Dong, Xiao-Rong; Zhang, Bei; Zhang, Xin-Tong; Liu, Jing-Zhuo; Ma, De-Sheng; Ma, Li
Abstract : Abstract: Cell death occurs in various tissues and organs in the body. It is a physiological or pathological process that has different effects. It is of great significance in maintaining the morphological function of cells and clearing abnormal cells. Pyroptosis, apoptosis, and necrosis are all modes of cell death that have been studied extensively by many experts and scholars, including studies on their effects on the liver, kidney, the heart, other organs, and even the whole body. The heart, as the most important organ of the body, should be a particular focus. This review summarizes the mechanisms underlying the various cell death modes and the relationship between the various mechanisms and heart diseases. The current research status for heart therapy is discussed from the perspective of pathogenesis.